2008
DOI: 10.1158/1541-7786.mcr-07-2115
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulator GeneCDC5L, a Potential Target for 6p12-p21 Amplicon in Osteosarcoma

Abstract: Osteosarcoma is a primary malignant tumor of bone arising from primitive bone-forming mesenchymal cells and accounts for f60% of malignant bone tumors. Our comparative genomic hybridization (CGH) studies have identified frequent amplification at 6p12-p21, 12q13-q15, and 17p11.2 in osteosarcoma. Of these amplified regions, 6p12-p21 is particularly interesting because of its association with progression and poor prognosis in patients with osteosarcoma. In an attempt to identify aberrantly expressed gene(s) mappi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 26 publications
(43 reference statements)
7
66
0
Order By: Relevance
“…The most commonly amplified genomic interval of 6p21-p23 harbors, among others, several candidate genes: angiogenesis-associated VEGFA, cell cycle-associated E2F3, CCND3, and RUNX2, and carcinomaassociated PTK7. These genes are directly or indirectly involved in the pathogenesis and pathways of malignant tumors, and amplifications have also been described in a high percentage of osteosarcomas (4,11,12,17,(37)(38)(39). In the present study, we found high amplification spots in 24% of the investigated tumors (Fig.…”
Section: Amplification Hotspotssupporting
confidence: 75%
See 1 more Smart Citation
“…The most commonly amplified genomic interval of 6p21-p23 harbors, among others, several candidate genes: angiogenesis-associated VEGFA, cell cycle-associated E2F3, CCND3, and RUNX2, and carcinomaassociated PTK7. These genes are directly or indirectly involved in the pathogenesis and pathways of malignant tumors, and amplifications have also been described in a high percentage of osteosarcomas (4,11,12,17,(37)(38)(39). In the present study, we found high amplification spots in 24% of the investigated tumors (Fig.…”
Section: Amplification Hotspotssupporting
confidence: 75%
“…There is not a single amplicon covering the whole central region of 6p; instead we found a few smaller hot spot regions harboring CCND3, RUNX2, and VEGFA. These genes have already been found to be overexpressed in osteosarcomas (38), and high expression of VEGFA has been correlated with a poor prognosis (40,41). Interestingly, the cell-cycle-associated E2F3, a downstream target of RB1, which has been found amplified and overexpressed in other tumors, e.g., in urothelial cancer (42), was the only gene located within a small amplified spot suggesting an alternative way to interfere with the RB1 pathway.…”
Section: Amplification Hotspotsmentioning
confidence: 93%
“…MDGA1 has been proposed as a new schizophrenia susceptibility gene involved in neuronal migration [35], meanwhile MDGA2 has been postulated as a novel autism susceptibility gene that shows a high similarity to contactin 4 (CNTN4), which has also been linked to this disease [36]. Moreover, MDGA1 expression has been found to be altered in tumor tissues [3,37]. Future studies to investigate the implication of the MDGAs in these human diseases should be promising.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, gain of 6p is associated with advanced stages of cancer [Seute et al, 2001;Chochi et al, 2009], metastasis [Tanami et al, 2005], tumor cell proliferation [Tomovska et al, 2001], and poor event-free survival [Lu et al, 2008]. When one considers rearrangements across the entire genome, gain and/or amplification of the region 6p21-p12 is one of the most frequent aberrations in solid tumors and hematologic cancers [Baudis and Cleary, 2001].…”
Section: P Is a Hot Spot For Rearrangement In Human Cancersmentioning
confidence: 99%
“…In human osteosarcomas, recurrent amplification at chromosome 6p21-p12 has been documented [Lau et al, 2004;Lu et al, 2008;Selvarajah et al, 2008;Sadikovic et al, 2009] and has recently been shown to be associated with clinical response [Sadikovic et al, in press]. Gain and amplification of murine chromosomal regions homologous to human chromosome 6p are also reported in conditional mouse models of osteosarcoma [Walkley et al, 2008].…”
mentioning
confidence: 99%